2013
DOI: 10.1089/ars.2012.4597
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of the Yeast Mitochondrial Thioredoxin Promotes Cell Death

Abstract: Mitochondrial Prx1 functions as a redox signaling molecule that oxidizes Trx3 and promotes apoptosis. This would mean that under conditions where Prx1 cannot detoxify mitochondrial ROS, it induces cell death to remove the affected cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 43 publications
1
37
0
1
Order By: Relevance
“…Because reduced Trx plays a critical role in cellular proliferation and viability (Scheme 1), excessive oxidation of Trx will lead to cell death (41). Recently, a study showed that oxidation of the yeast mitochondrial thioredoxin promotes cell death (45).…”
Section: Discussionmentioning
confidence: 99%
“…Because reduced Trx plays a critical role in cellular proliferation and viability (Scheme 1), excessive oxidation of Trx will lead to cell death (41). Recently, a study showed that oxidation of the yeast mitochondrial thioredoxin promotes cell death (45).…”
Section: Discussionmentioning
confidence: 99%
“…It is conceivable that such an intracellular redox-dependent signaling pathway dampens the propagation of mutants that produce increased levels of mitochondriaderived oxidative stress in order to prevent the distribution of malfunctional mitochondria. A recent study showed that oxidative stress in mitochondria leads to cell death in yeast by inducing caspase-mediated apoptosis (19). The yeast metacaspase Yca1 is known to be activated by hydrogen peroxide although the details of this apoptotic signaling pathway in yeast are not entirely clear (33).…”
Section: Discussionmentioning
confidence: 99%
“…The opening of this pore is accompanied by membrane potential (Δι) collapse, calcium release, uptake of electrolytes and water, matrix swelling and ruptures of the mitochondrial outer membrane [42] . As a consequence, several factors are released into the cytosol including cytochrome c, apoptotic peptidase activating factor 1 (apaf-1), apoptosis-inducing factor (AIF) and caspase family members, which participate in apoptosis pathways [43][44][45] . Several agents, such as Ca 2+ , thiol oxidants, reactive oxygen species (ROS), and/or members of the Bcl -2 family of proteins can regulate cell death or survival by interference with MPTP opening [46][47][48] .…”
Section: Discussionmentioning
confidence: 99%